2014
DOI: 10.1126/science.1254390
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a single loss of mineralized teeth in the common avian ancestor

Abstract: Edentulism, the absence of teeth, has evolved convergently among vertebrates, including birds, turtles, and several lineages of mammals. Instead of teeth, modern birds (Neornithes) use a horny beak (rhamphotheca) and a muscular gizzard to acquire and process food. We performed comparative genomic analyses representing lineages of nearly all extant bird orders and recovered shared, inactivating mutations within genes expressed in both the enamel and dentin of teeth of other vertebrate species, indicating that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 95 publications
6
99
0
Order By: Relevance
“…Our analyses have revealed that, similar to observations in other lineages (Wang et al 2006;Meredith et al 2014), gene loss through pseudogenization has had a significant impact on the evolution and diversification of pangolin genomes and their biology. We detected and validated pseudogenes in pathways related to multiple morphological or physiological functions including dentition, vision, and immunity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our analyses have revealed that, similar to observations in other lineages (Wang et al 2006;Meredith et al 2014), gene loss through pseudogenization has had a significant impact on the evolution and diversification of pangolin genomes and their biology. We detected and validated pseudogenes in pathways related to multiple morphological or physiological functions including dentition, vision, and immunity.…”
Section: Discussionsupporting
confidence: 54%
“…S7.1,S7.2). Loss of function of these genes through pseudogenization has also been reported in other edentulous vertebrates such as toothless baleen whales, birds, and turtles (Meredith et al 2014).…”
Section: Pangolin-specific Phenotypesmentioning
confidence: 99%
“…In fact, there are strong hints that large deletions caused a substantial level of gene loss in birds (274 protein-coding genes) with potentially profound phenotypic consequences (46,81,82). The foreseeable improvement of genome assembly via third-generation sequencing (e.g., long-read sequencing and gap filling; see ref.…”
Section: Dna Gain and Loss Analysis Reveals The Elasticity Of Avian Amentioning
confidence: 99%
“…Using the phylogenomic backbone and the information about all genes that are present in a genome assembly and annotation, Meredith et al (2014) found that mineralised teeth were lost only a single time in the common avian ancestor. In all of the 48 bird taxa of the genome project, the genes that are responsible for the formation of dentin and enamel were inactivated by mutations, whereas these genes are still active in crocodiles.…”
Section: A First Phylogenomic Avian Tree Of Lifementioning
confidence: 99%